2012
DOI: 10.1371/journal.pone.0042612
|View full text |Cite
|
Sign up to set email alerts
|

FASCAPLYSIN as a Specific Inhibitor for CDK4: Insights from Molecular Modelling

Abstract: Cyclin-dependent kinases (CDKs) play a key role in the cell cycle and are important anti-cancer drug targets. The natural product fascaplysin inhibits CDK4 with surprising selectivity (IC50 = 0.4 µM) compared to the close homolog CDK2 (IC50 = 500 µM). Free energy calculations of the positively charged fascaplysin and an uncharged iso-electronic derivative in the CDK2 and CDK4 inhibitor complexes indicate that the positive charge of fascaplysin is crucial for selectivity. This finding will guide further improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 86 publications
0
38
0
1
Order By: Relevance
“…Crystal structures of STAT3 (PDB:1BG1), PARP (PDB: 1WOK), p38 alpha (PDB: 1OVE), NF-kB (PDB:1VKX), AKT (PDB: 2JDO), CDK6 (PDB: 1X02), mTOR (PDB:4JSP), MKK4 (PDB:3ALN), JAK (PDB:3EYG), BCL-2 (PDB: 2O21), MEK1 (PDB: 3VVH), CHK1 (PDB: 2E9P), PI3K (PDB:3L54), and CHK2 (PDB: 2WTJ) protein structures were retrieved from Protein Data Bank (PDB) and imported to Discovery studio work environment. The structure of CDK4/Cyclin D1 was downloaded from previously reported work [25]. Later, the proteins were prepared by removing HETATM lines other than co-factors and unwanted water molecules from the structure.…”
Section: In-silico Docking Analysismentioning
confidence: 99%
“…Crystal structures of STAT3 (PDB:1BG1), PARP (PDB: 1WOK), p38 alpha (PDB: 1OVE), NF-kB (PDB:1VKX), AKT (PDB: 2JDO), CDK6 (PDB: 1X02), mTOR (PDB:4JSP), MKK4 (PDB:3ALN), JAK (PDB:3EYG), BCL-2 (PDB: 2O21), MEK1 (PDB: 3VVH), CHK1 (PDB: 2E9P), PI3K (PDB:3L54), and CHK2 (PDB: 2WTJ) protein structures were retrieved from Protein Data Bank (PDB) and imported to Discovery studio work environment. The structure of CDK4/Cyclin D1 was downloaded from previously reported work [25]. Later, the proteins were prepared by removing HETATM lines other than co-factors and unwanted water molecules from the structure.…”
Section: In-silico Docking Analysismentioning
confidence: 99%
“…The marine natural product fascaplysin is known to be one of the most potent cyclin‐dependent kinase 4 (CDK4) specific inhibitors . However, fascaplysin exhibits high toxicities due to its DNA intercalating properties .…”
Section: Tubulin Kinase Dual Inhibition In Anticancer Treatmentmentioning
confidence: 99%
“…The marine natural product fascaplysin is known to be one of the most potent cyclin-dependent kinase 4 (CDK4) specific inhibitors. 150,170 However, fascaplysin exhibits high toxicities due to its DNA intercalating properties. 150,171 As of recent, Mahale et al 150 identified a nonplanar tryptoline analogue, BPT (66), as potent CDK4 D1 enzyme specific inhibitor and did not demonstrate DNA binding properties, primarily due to its planar structure.…”
Section: Cyclin-dependent Kinasementioning
confidence: 99%
“…In the sponge, fascaplysin (2) is the major compound which represents 0.02% of the lyophilized sponge weigh. It exhibits many biological activities including cytotoxicity against tumoral cells (Segraves et al 2004;Shafiq et al 2012;Hamilton 2014;Cells et al 2015;Kumar et al 2015), antimicrobial activities (Roll et al 1988), and the inhibition of acetylcholinesterase (Bharate et al 2012;Manda et al 2016). For microbial disease treatments in aquaculture, fascaplysin (2) is not ideal.…”
Section: Fascaplysinmentioning
confidence: 99%